2009
DOI: 10.1590/s0101-20612009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do mercado consumidor de "água aromatizada": hábitos e motivações para o consumo

Abstract: IntroduçãoNas últimas décadas, a preocupação com a saúde está cada vez mais visível no comportamento da população. A busca pela qualidade de vida se estende aos cuidados com a alimentação, caracterizada por uma crescente demanda por produtos saudáveis e com características nutricionais e sensoriais próximas dos alimentos in natura. Baseada nisto, a indústria alimentícia está cada vez mais atenta aos desejos do consumidor e investe na formulação e produção de novos produtos, concentrando seus esforços na área d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Most participants indicated that they typically drink mate prepared from tea bags, most frequently with sugar at home before they went to bed. Other studies have also indicated the home as the main venue to consume some beverages (Arruda et al, 2009;Endo, Bertoldi, Pinheiro, Arruda, & Minim, 2009).…”
Section: Consumer's Profilementioning
confidence: 99%
“…Most participants indicated that they typically drink mate prepared from tea bags, most frequently with sugar at home before they went to bed. Other studies have also indicated the home as the main venue to consume some beverages (Arruda et al, 2009;Endo, Bertoldi, Pinheiro, Arruda, & Minim, 2009).…”
Section: Consumer's Profilementioning
confidence: 99%
“…The search for quality of life extends to nutritional care, characterized by an increasing demand for healthy products with nutritional and sensory characteristics close to fresh foods (Endo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Searches invest in water-based products incorporating flavors, vitamins and/or minerals; therefore known in the United States and Europe as "waters with added value" (Endo et al, 2009). Recently, industrialized beverages from many brands, called "low-calorie soft drinks" also appeared on the market (products with slightly aerated sugar zero), which constitutes an attractive to consumers in competition with carbonated mineral water.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, a pesquisa de mercado tem se mostrado uma ferramenta muito útil para elucidar o comportamento dos consumidores de diversas categorias de produtos. Diversos trabalhos com abordagens distintas, aplicados em diferentes segmentos de mercado têm se dedicado a este tipo de pesquisa e contribuído para identificar as preferências, hábitos e costumes, o perfil socioeconômico, imagem de marca, intenções de compra e análise de participação do mercado, entre outras características do mercado (Endo et al, 2009). Diante deste contexto, o objetivo deste estudo consistiu em conhecer e caracterizar o comportamento de compra do consumidor soteropolitano de refrigerantes, identificando seus hábitos de consumo e decisões que são tomadas no momento da compra do produto, os grupos de referência, e os atributos considerados importantes para a sua decisão de compra.…”
Section: Introductionunclassified